Spatially and temporally resolved monitoring of doping polybenzimidazole membranes with phosphoric acid - Arslan, Funda; Böhm, Thomas; Kerres, Jochen; Thiele, Simon (Journal of Membrane Science, 2021)
Polybenzimidazole-based membranes in high temperature proton exchange membrane fuel cells require doping with phosphoric acid to enable proton conductivity. The level of phosphoric acid doping is traditionally determined by titration or weighing, but these methods only provide limited information, since they do not offer spatial resolution. We show that confocal Raman microscopy can not only provide information on the level of doping, but in addition about the spatial distribution of the dopant. We prove that doping is a diffusion-limited process, leading to a spatially inhomogeneous distribution of phosphoric acid unless doping is performed to saturation. Further, evidence of a slow redistribution of the dopant within a freestanding membrane under ambient conditions is provided. Confocal Raman microscopy can be used as a non-invasive measurement tool to investigate status and progress of doping a membrane with phosphoric acid.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Acid doping level (ADL); Acid uptake (AU); Fuel cells (FCs); High temperature (HT); Phosphoric acid (PA); Polybenzimidazole (PBI); Polymer electrolyte membrane; Raman spectroscopy